1999
DOI: 10.1016/s0741-5214(99)70387-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of distal emboli in patients with peripheral arterial stenosis before and after iliac angioplasty: A prospective study

Abstract: ES can be detected in the common femoral artery with Doppler ultrasound scanning in patients with iliac artery stenosis both before and soon after iliac PTA despite preangioplasty aspirin and intra-angioplasty heparin therapies. The occurrences of ES were particularly frequent in the 2 hours after PTA. This technique can be used further to study factors that control plaque stability and to evaluate the effect of therapeutic interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 30 publications
(49 reference statements)
0
18
0
Order By: Relevance
“…In similar studies emboli were detected by ultrasound monitoring during iliac intervention. 9,10 These studies involved numbers too small to make conclusions on risk factors for the development of clinically or angiographically significant embolization.…”
mentioning
confidence: 99%
“…In similar studies emboli were detected by ultrasound monitoring during iliac intervention. 9,10 These studies involved numbers too small to make conclusions on risk factors for the development of clinically or angiographically significant embolization.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] Thus far, attempts at measuring embolization during peripheral arterial interventions have been few and with small numbers of patients. [9][10][11] The purpose of this prospective study was to evaluate the incidence of distal embolization during percutaneous SFA intervention using continuous transcutaneous Doppler ultrasound. We quantified the rate of embolization at various phases of intervention, such as during guidewire crossing, balloon angioplasty, stent deployment, and directional atherectomy with either the SilverHawk (FoxHollow Technologies, Redwood City, Calif) device or the Spectranetics excimer laser device (Spectranetics Corporations, Colorado Springs, Colo), and analyzed angiographic and clinical sequelae of these events.…”
mentioning
confidence: 99%
“…[12][13][14] Embolic signals have also been observed via Doppler ultrasound at the level of the common femoral artery in 90% of patients undergoing iliac artery angioplasty despite the authors attempt to limit this complication with pre-procedure aspirin and intra-procedure heparin administration. [15] Due to the lack of randomized prospective studies, the benefit provided by an EPD is uncertain. Early experience has demonstrated that the device can be used safely and effectively in patients with appropriate anatomy.…”
Section: Discussionmentioning
confidence: 99%